Nilai-Nilai Pendidikan Islam dalam Budaya Nganggung dan Implikasinya terhadap Solidaritas Umat di Kecamatan Mendo Barat Kabupaten Bangka - Suparta, Suparta (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2017)
The Values of Islamic Education in Nanggung Culture and Its Implication on Solidarity of People in Mendo Barat Sub-district of Bangka Regency. Each region has a different culture, including the existing culture in the District of Bangka Belitung. However, not all cultural heritage of the ancestors have an education of Islamic values. In Bangka Belitung, there is a culture of ancestral heritage that has an education of Islamic values, namely value education that is revealed in the culture of such as religious values, ethics, social values, ukhwah Islamiyah value, and gotong royong value. These values can ultimately have implications for the solidarity of the people in Bangka district. This paper concludes that Nganggung culture continues to be maintained and preserved in Bangka regency. As a tradition of Bangka community that has been done for generations, nganggung has good values of local wisdom and even including the Islamic tradition. This tradition can also instill a noble value education which is emphasized in the teachings of Islam. These values are like social values by strengthening the relationship, the value of psychiatric education, the value of togetherness or solidarity, and aesthetic value.